Knee Imaging Following Anterior Cruciate Ligament Reconstruction: The Surgeon's and Radiologist's Perspectives - Srinivasan, Ramya; Wan, Jennifer; Allen, Christina R.; Steinbach, Lynne S. (Seminars in Musculoskeletal Radiology, 2018)
Anterior cruciate ligament (ACL) tears are common injuries that if left untreated can result in chronic instability, cartilage damage, meniscal tears, and ligamentous injuries, eventually leading to early osteoarthritis. ACL reconstruction surgeries are therefore increasingly being performed. Despite the fact that most patients achieve excellent postoperative results, patients can present with recurrent instability and pain. These patients often undergo imaging with radiographs, magnetic resonance imaging, and/or computed tomography. An understanding of the imaging appearance of the normal ACL reconstruction and common causes of failure is therefore essential for the interpreting radiologist. This article reviews surgical techniques for ACL reconstruction, highlighting recent technical advances, the normal imaging appearance after ACL reconstruction, etiologies for reconstruction failure, and the diagnosis of these with the aid of imaging.
Keywords: ACL reconstruction; ACL reconstruction complications; ACL reconstruction MRI; ACL graft tear